MPR DAN URGENSI GARIS BESAR HALUAN NEGARA DALAM SISTEM KETATANEGARAAN INDONESIA - Setya Nugraha, Harry (Faculty of Law, Parahyangan Catholic University, 2019)
This article, using a normative-juridical approach, discusses the issue whether Indonesia should re-introduce and re-instate the Guidelines of State Policy which was abolished in 1998, into the existing constitutional system. The author discusses a number of reasons of why re-instatement should be considered necessary. One important finding is that a new model of the Guidelines of State Policy should be made and utilised as a binding directive for state and government institutions at the central as well as regional and local level of governance.